The effects of liabilities of age and size on autonomous sub-units of established firms in the steel distribution industry - Venkataraman, S.; Low, Murray B. (Journal of Business Venturing, 1994)
This study investigates the effects of organizational sub-unit age and size on three dimensions of customer relationships: response satisfaction, service-depth satisfaction, and perceived cooperation. The study is motivated by the frequent suggestion that one way to introduce an entrepreneurial climate into large and/or old organizations is to create small, autonomous sub-units. By establishing internal start-ups, mature organizations can achieve the flexibility and innovation associated with youth and small size. However, this argument only holds if it is found that being embedded in an established firm enables the sub-units to overcome some of the problems normally experienced by independent start-ups. Liabilities of age and size hypotheses suggest that there are advantages and disadvantages to youth and old age, and correspondingly, to small and large size. Often these advantages and disadvantages are complementary. Consistent with these insights we offer the following three sets of hypotheses on the effects of sub-unit age and size on the relationships between an organizational sub-unit and its customer population.